NEGOCIACIONES INTERNACIONALES HACIA LA LIBERACIÓN HEMISFÉRICA: ALCA - TLCPEU - OMC - Bouby Tolentino, Fancisca (2004)
Critical analyses of international trade negotiations being made during the last fewyears pertaining to Peruvian participation in diverse processes, zeroing mainly in Free Trade American Area (FTAA), the Free Trade Agreement with USA and the World Trade Organization (WTO) are made in this paper.